Chile : Selected Issues. (IMF Staff Country Reports; Country Report, 2000)
This paper presents four studies on selected issues of the Chilean economy. The first two studies address matters relevant to the implementation of monetary policy, motivated in part by Chile's recent adoption of an enhanced framework for inflation targeting. The degree of external vulnerability of the Chilean economy, drawing heavily on international evidence, is also discussed. Finally, this paper also includes a statistical appendix, and three annexes summarizing certain aspects of Chile's economic policy regime. Forecasting inflation is an essential element of any inflation targeting regime.